Analisis Kemampuan Analytical Thinking Skill Siswa SMA Swasta Masehi Berastagi dalam Perspektif Bimbingan Karir - Br Bangun, Risda Heldriyana; Zuzanti, Zakia (Lembaga Yasin AlSys, 2025)
Analytical thinking is a critical cognitive skill that supports students in making rational and realistic career decisions. This study is motivated by the low level of analytical thinking ability among senior high school students, which contributes to their unpreparedness in determining career direction. The objective of this research is to analyze the level of analytical thinking ability among students at SMA Swasta Masehi Berastagi from the perspective of career guidance. A descriptive quantitative approach was employed using a survey method. The sample consisted of 18 students selected through total sampling. The research instrument utilized a Guttman Scale comprising 18 statements based on three dimensions of analytical ability as outlined by Anderson and Krathwohl: differentiating, organizing, and attributing. The analysis revealed that students' analytical thinking ability was at a moderate level (58%). The organizing aspect achieved the highest score (62%), followed by attributing (57%) and differentiating (55%). These findings suggest that while students demonstrate a fair ability to organize information, they struggle to distinguish relevant information and relate it to career decision-making factors. The study concludes that there is a need to strengthen analytical thinking skills through career guidance services that integrate reflective strategies and self-analysis activities. The practical implication is that guidance counselors should develop counseling approaches grounded in analysis and self-reflection to better support students’ career exploration and planning in a more focused and in-depth manner.